Milt Motility, Viability, and Abnormality of the Indonesian Java Barb, Barbonymus gonionotus (Bleeker, 1850) after Frozen - ., Abinawanto; ., Aisyah (New Visions in Science and Technology Vol. 7, 2021)
The Indonesian Java barb, Barbonymus gonionotus is one the indigenous fish and had has an economic value. The objective of study was to evaluate the effect of different glycerol concentrations on the milt quality of Barbonymus gonionotus after frozen. The concentrations of glycerol used in this study were 0%, 5%, 10%, 15%, and 20%, respectively. Semen was collected by hand stripping method. The equilibration was conducted at 4ºC for 10 minutes, and milt was frozen at -34ºC for 24 hours. Thawing was performed at 45ºC for 30-60 seconds. Volume, pH, and colour of fresh semen were observed. Milt motility, viability, and abnormality were also evaluated, before and after frozen. Based on the Dunnet test, 15% of glycerol showed the highest (P>0.05) milt viability (68.69 ± 5.95%), while either 10% or 15% of glycerol showed the higher (P>0.05) of milt motility (88.36 ± 4.77)% and (85.45 ± 10.98)%, respectively. Milt abnormality were not different (P<0.05) among treatment groups. Fifteen percent of glycerol was tend to the optimum concentration to preserve sperm motility and viability at -34°C for 24 hours.